Dėl prūsų etnonimo reikšmės ir kilmės - Karaliūnas, Simas (Baltistica, 1977)
On the meaning and etymology of the Оld Пrussian ethnic name The attested adjective OPr. prūsiskan “Prussian” evidently is derived from the Old Prussian noun *prūsis resp. *prūsas. It is also assumed that the Old Prussian ethnic name might have developed by the semantic change “increase, grow, rise”, “crowd, throng, multitude” which may be illustrated by several examples (cf. the etymologies of Lith. tautà, liáudis, Lat.plēbs, Gr. πλη̃ϑος etc.). It is Lith. prùsti and Latv. praũstiês that just have the needed meaning “increase, grow, rise”.